The Legality Principle Application in Indonesian Criminal Law System - Achmad Bustomi (Nurani Hukum, 2021)
The application of legality principle in Indonesia criminal law system is the main tool in the enforcement of criminal law. The nature of legal certainty attached to the principle of legality makes criminal law one of the fields of legal science that is certain in the eyes of the law. Because it attaches to clear and firm legal frames, it is an instrument of guidance and limitation in applying concrete cases. This paper analyzes how the principle of legality in criminal law can make the law a certainty. The principle of legality limits in detail and carefully what actions can be punished. The results of the study state that in Indonesia, based on the principle of legality, criminal acts must be regulated in writing. However, some areas still use customary law. Then the nature of criminal law may not apply retroactively.